AUDITORS’ WORKING ENVIRONMENT AND CORPORATE INVESTMENT DECISIONS IN NIGERIA - ADENIJI , Yisa Ayinla (JOURNAL OF ECONOMICS AND ALLIED RESEARCH, 2021)
Prior to the advent of COVID-19 pandemic ravaging the entire world economy, corporate and institutional investors had suffered huge financial losses as a result of audit failures. Despite this situation, investment decisions are generally premised on audited financial statements. The study therefore examined the effect of auditors’ working environment (proxied by top management support, training and development, physical work environment and autonomy to implement audit techniques) on corporate investment decisions in Nigeria. The study adopted survey research design, using purposive sampling technique to select 150 respondents. A combination of self-designed and adopted structured questionnaire was used to collect the data. The instrument was validated using Cronbach’s alpha. The reliability coefficient of the constructs ranged from 0.647 to 0.907. The response rate was 73%. Data were analyzed using descriptive and inferential statistics. The study found that auditors’ working environment had no significant influence on corporate investment decision (Adj: R2=0.068; F (4, 104) = 1.905; >0.05). But top management support and physical work environment had significant impact on corporate investment decisions. It was recommended that investors and decision makers take cognizance of auditors’ physical work environment together with management support for auditors as a premise for decision making.